Perencanaan Struktur Gedung 5 Lantai Dengan Analisis Program Etabs Kampus Sekolah Tinggi Teknologi Pagar Alam (STTP) - Vike Itteridi; Idwin Shaleh (JURNAL ILMIAH BERING'S, 2017)
Over time, the number of students from the Pagar Alam High School from year to year has increased rapidly, not only from the city of natural fences, the increase in students began to arrive from other cities with the increasing number of students who were not matched with infrastructure such as classrooms. teaching and learning activities will be a little disturbed. Therefore the provision of learning space facilities must be considered and the development planning vertically so that it can utilize the land as best as possible. In this study planning the construction of a class building at the Pagar Alam College of Technology. done by manual calculation to get the dimensioning of columns, beams, plates and the area of ​​reinforcement. After the manual calculation was obtained it was only analyzed with the help of the Etabs program, after analysis was carried out with the Etabs program there were several results from manual calculations that were unable to withstand the workload so that modifications were made to the column and the number of reinforcement. In planning, it requires special assessment in accordance with the requirements of SNI 03-2847-2002 and SNI 03-1726-2002.